2015
DOI: 10.1007/s00428-015-1739-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of urothelial bladder cancer in patients less than 40 years old

Abstract: Urothelial bladder cancer (UBC) is rare in young patients and as a result little information as to tumor type and clinical course are available. We present clinicopathological data of a large series of patients less than 40 years with bladder carcinoma. We included in this retrospective study covering the period from 1992 to 2013 patients less than 40 years with a first diagnosis of bladder cancer. Lesions were classified according to the WHO 2004 classification by uropathologists of ten centers. Stage, grade,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
127
2
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(140 citation statements)
references
References 14 publications
7
127
2
4
Order By: Relevance
“…Major environmental risk factors are smoking or professional exposure during several years (probably around 20 years) (15). Male predominance is noted in most studies, similar to that reported in older patients, but also similar to studies in very young patients under 20 years (9 Up to date, only one original study with more than 150 cases for UBC in young patients has been published and another with more than 100 cases (11,14). In the largest study with more than 150 patients, the authors show that most patients displayed not invasive urothelial carcinomas; carcinoma in situ was a rare finding.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Major environmental risk factors are smoking or professional exposure during several years (probably around 20 years) (15). Male predominance is noted in most studies, similar to that reported in older patients, but also similar to studies in very young patients under 20 years (9 Up to date, only one original study with more than 150 cases for UBC in young patients has been published and another with more than 100 cases (11,14). In the largest study with more than 150 patients, the authors show that most patients displayed not invasive urothelial carcinomas; carcinoma in situ was a rare finding.…”
Section: Discussionsupporting
confidence: 77%
“…Nevertheless, many authors make a difference between <20 years and < 40 years, knowing that the group 30-40 years approaches to the patients diagnosed with UBC in older age (14). The second problem are the cases observed in children or young adults, mostly under 15 years, frequently first treated in pediatric structures, and later followed-up in adults hospitals, those patients might get lost in studies.…”
Section: Discussionmentioning
confidence: 99%
“…(6) In contrast, a paper on 152 young bladder cancer patients reported that in those less than 30 years of age, 40.3% had a papillary urothelial neoplasia of low malignant potential. (11) In addition, the field is complicated by the variability of definitions of what constitutes a “young patient”. Most published series define “young” as less than 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
“…In their study with 152 UBC patients under 40, Comperat and colleagues reported that the most important factors that affect disease prognosis are histopathological grade and tumour stage. 1 In our study, we also determined that both tumour grade and stage affect recurrence and progression. Bladder cancers in younger patients were single-focused tumours.…”
Section: Discussionmentioning
confidence: 93%
“…Low-grade papillary carcinomas have an advantage of longer survival rates, even though they frequently recur since they are usually not muscle invasive. 1 On the contrary, high-grade urothelial cancers tend to be invasive in nature and carry a serious risk of progression which can lead to metastasis. These tumour occurrence rates peak around the 6th decade of life.…”
Section: Introductionmentioning
confidence: 99%